A Systematic Review of How Usability and Accessibility Drive Satisfaction in Next-Gen E-Government - Progresto, Mohammad Bintang; Arviansyah, Muhammad Rifqi (Dinasti Publisher, 2026)
This study discusses user satisfaction in e-government service using the framework of communication theory, specifically the usability-accessibility standard and the Technology Acceptance Model (TAM). The primary aim is to analyze how usability and accessibility affect user satisfaction on various e-government platforms. This will be based on communications and information system theories. The study does not formulate a strict hypothesis but would be open to well-considered systems that are well-correlated with citizen satisfaction. A systematic literature review (SLR) was conducted, combining 54 peer-reviewed papers from 2008 to 2024. Utilizing PRISMA guidelines, articles were chosen and analyzed thematically within six research questions (RQ1–RQ6). Methods employed were qualitative and quantitative, including questionnaires, usability testing, and model-based measurement (e.g., TAM, DeLone & McLean IS Success Model) as the primary framework of analysis. Results show that usability (32 studies) and accessibility (in 32 combined cases) are standard drivers of satisfaction, particularly in Government-to-Citizen (G2C) services, which made up 85% of the articles. Technical limitations, poor interface design, and infrastructural deficiency were the most cited hindrances. The findings validate TAM's explanatory power and coincide with previous communication-oriented usability models, such as ISO 9241. Though user-centered design is cited most, it’s not examined as a distinct variable for accessibility in this review. This review concludes that e-government user satisfaction is defined by a combination of technical, design, and communication variables. Future research must concentrate on accessibility as a standalone measure and broaden research on Government-to-Government (G2G) services to gain a comprehensive understanding.